Distinctive features of the biochemical composition sea buckthorn fruits of Altai selection - E. D. Rozhnov; M. N. Shkolnikova; O. V. Chugunova (Современная наука и инновации)
The article presents data on the biochemical composition of sea buckthorn fruits zoned and grown on the territory of the Altai Territory. The information on the distinctive features of the most common varieties in the selection of Azhurnaya, Altai, Inya, Chechek, Chuiskaya is summarized. The biochemical composition of sea buckthorn fruits of these varieties has been studied. A wide variability in the content of sugars, titrated acids, ascorbic acid and aroma-forming compounds affecting the taste characteristics of sea buckthorn fruits and determining its further use has been established.